The Implementation Of Game Theory Models In Transportation - Yuhelson Yuhelson (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2020)
In most industries a central characteristic of competition is that firm are mutually dependent: firms feel the effects each others’ moves and are prone to react to them (Porter, 1980). This situation, economists call an oligopoly. An oligopoly has few sellers, with interdependent pricing decisions among the larger firms iin the industry (Nafziger, 1997). This interdependency is the essence of competition.